2020
DOI: 10.21203/rs.2.22494/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dexamethasone can attenuate the pulmonary inflammatory response via regulation of the lncH19/miR-324-3p cascade

Abstract: Objective: To investigate lncRNAs and their roles in regulating the pulmonary inflammatory response under treatment of Dexamethasone (Dex).Methods: IL-1β (10 ng/mL) and LPS (1 μg/mL) was used to induce an inflammatory cell model with A549 cells, and the results showed that IL-1β performed better against LPS. Dex with different concentration was used to attenuate inflammation by IL-1β, and its effect was assessed by RT-PCR to detect the inflammatory related mRNA, including IKβ-α, IKKβ, IL-6, IL-8, and TNF-α. An… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
0
1
Order By: Relevance
“…Comparisons of isofraxidin with dexamethasone in the present study showed that both agents suppress TPA-induced IL-6 mRNA expression in HuH-7 cells at 50-200 µM. However, a study using the A549 human lung cancer cell line, showed that dexamethasone suppressed IL-6 mRNA expression at 10-10,000 nM following IL-1β stimulation [34]. Determining whether isofraxidin suppresses IL-6 mRNA expression at lower concentrations (less than 50 µM) in HuH-7 cells under improved culture conditions is under investigation.…”
Section: Discussioncontrasting
confidence: 61%
“…Comparisons of isofraxidin with dexamethasone in the present study showed that both agents suppress TPA-induced IL-6 mRNA expression in HuH-7 cells at 50-200 µM. However, a study using the A549 human lung cancer cell line, showed that dexamethasone suppressed IL-6 mRNA expression at 10-10,000 nM following IL-1β stimulation [34]. Determining whether isofraxidin suppresses IL-6 mRNA expression at lower concentrations (less than 50 µM) in HuH-7 cells under improved culture conditions is under investigation.…”
Section: Discussioncontrasting
confidence: 61%